Ethnic enclosure in Soviet and Post-Soviet school textbooks - Rouvinski, Vladimir (Universidad de Hiroshima, 2007)
In this paper, we first explore the process of history writing and teaching in Soviet autonomies using the concept of ethnic enclosure as a framework to examine the way the distant past is presented in history textbooks published locally in the Soviet Union. We then show the conflicting character of ethnic historical narratives in the textbooks of rival ethnic groups and, next, discuss the legacy of the Soviet policy of ethnic enclosure as reflected in school textbooks published after the demise of the Soviet Union.
Keywords: Ciencias sociales; Social sciences; Ciencia política; Political science; Unión Soviética; Soviet Union